A CFD analysis on improving lettuce canopy airflow distribution in a plant factory considering the crop resistance and LEDs heat dissipation. (December 2020) - Fang, Hui; Li, Kun; Wu, Gang; Cheng, Ruifeng; Zhang, Yi; Yang, Qichang
Abstract : In a plant factory, improper design of the indoor ventilation system may cause tip burn on lettuce plants due to the existence of stagnant air in the leaf boundary layer and low transpiration rates. In this study, three types of air ducts with different pore numbers and diameters were designed to generate a constant horizontal airflow on the surface of plant canopy. A three-dimensional computational fluid dynamics (CFD) model was established to analyse the airflow pattern on the crop canopy under different ventilation modes in a single cultivation bed. For this simulation model, the lettuce leaves were treated as a porous medium, and the drag coefficient (CD ) was assumed to be 0.02, which resulted in a permeability ( K p ) and nonlinear momentum loss coefficient ( C F ) of 0.02 and 0.134, respectively. The LED lamps were set as the energy source, and the heat released was calculated to be 297.5 kW m −3 . All the data above were validated. Three Designs with different pore numbers and diameters were simulated to predict the distribution of airflow. The design with 12 pores and 15 mm diameter was predicted to give the highest percentage of mean air velocity between 0.28 m s −1 and 1.04 m s −1 on the lettuce canopy surface, at 70.3%. This duct design is recommended as the best of the three Designs in this study. Highlights: The viscous and inertial resistance were 50 m -2 and 2 m -1, respectively. The LED lamp with a constant heat generation of 297525 W m -3 . The percentage of air velocity at the lettuce canopy surface between 0.28 m s -1 and 1.04 m s -1 was 70.3%. A tube of 12 pores each with a diameter of 15 mm is recommended for ventilation.